Impact of HIV/AIDS on Quality of Life in People Living with HIV (PHLV) and Their Caregivers’ – A Mix Method Study - Binal Prajapati; Parimal Gurjar; Krunal Modi; Dhiren Amin; Devanshi Jani (Universitas Airlangga, 2026)
Antiretroviral therapy (ART) has changed the life expectancy of PLHIV patients, but not the quality of life (QoL). Caregivers of PLHIV are also facing social rejection, stigma, and many more problems, similar to those of PLHIV patients. The study was designed as a mixed-method study to document the Quality of life of HIV/AIDS Patients in a tertiary care hospital. The first aspect was the quantitative part, which included the World Health Organization Quality of Life Brief Version (WHO QoL BREF), which focused on the quality of Life of PLHIV. The second aspect focused on the qualitative part of this study, which included the in-depth interviews of caregivers of HIV Patients, trying to explore the different problems faced by caregivers of PLHIV, like social, family, health, economic, mental, stigma, etc., in the antiretroviral therapy (ART) center. The overall QoL score was 84.27±8.7. Overall QoL ranges from a minimum of 55.6 to a maximum of 101.8. The highest score, 20 out of 20, was observed in the physical domain, the independence level domain, and the SPRB (spirituality, personal and religious beliefs) domain. The lowest score, 4 out of 20, was seen in the social relationship and SPRB domains. As per the caregivers’ perspective, participants reported stigma, discrimination, and separation by their close relatives and society. In summary, the study shows that quality of life is affected by multiple variables, such as gender, age, residential area, education, socioeconomic class, and marital status. The study also concludes that caregivers of PLHIVs have to face stigma, discrimination, family rejection, society/community rejection, financial constraints, daily challenges and burden, health care facilities issues, etc.